Investigation of Convaren’s stimulating effect on immune organs of mice - Porsokhonova, Komila; Agzamov, Rustam (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Investigation of Convaren’s immunostimulating action on white mice used to prove its effectiveness as a new immunomodulatory drug that then may be used by humans for treatment of infectious, tumor, systemic, and other diseases followed by decrease of immune system function. Methods: In this investigation were observed immunomodulating effects of Convaren on immune organs of mice (spleen, thymus, mesenteric lymph nodes, bone medulla). All effects were estimated due to the amount of antibody producing cells (APC) in their spleen, amount of APC calculated on whole organ and on 106 spleen cells, amount of nucleus containing spleen cells, common amount of nucleus containing cells in thymus, mesenteric lymph nodes, and bone medulla. Results: Convaren in doses 50 and 100 mg/kg significantly increases amount of cells in thymus and bone medulla, but significant increase of cell amount in lymph nodes was observed just with dose 50 mg/kg. It shows that dose 50 mg/kg is optimum, with which the cell proliferation processes in central and peripheral immune organs are expressed maximally. Smaller dose of Convaren has a little better stimulating effect than the higher one. Conclusions: New drug Convaren has a high immunostimulating activity in mice’s organisms. Due to its low toxicity, availability of raw materials and not hard production and transportation Convaren may be a cost-effective drug for the Asian region.